Ceramoh Agama (religion explanation): Spactial Practice for Negotiation and Traditional Malay Muslim’s Religious Movement - มาหะมะ อัสรี (Journal of Social Sciences, Chiang Mai University, 2019)
This article focuses on religious movement of the traditional Muslim in Thailand under modernization driven by Thai state and “Islamization”. This way encourages Muslims gather to seek for the knowledge answer and understand Islam principle and new phenomena led by the religious leaders. These Muslims are from various places, both male and female, occupations, social levels, but wear the traditional local custom which represents Malay identity. Ceramoh Agama is obviously a religious practical space aiming to interpret Islamic principle and to understand social problems such as Islam and democracy, financial interest and Muslim society, or controversial religious discussion among Islamic group. This movement significantly indicates identity as cultural practice to contest space with neo-Muslim, capitalism and modernity. Thus, Ceramoh Agama becomes the contested space through responding, representing, reviewing themselves, and being resistant to adapt to social change.